The Use of Endomycorrhiza in Rehabilitating Matured Cocoa Stands - Maria Viva Rini, (1996)
A pot experiment was conducted to study the effectiveness of two VAM species in enhancing growth of cocoa seedlings. Cocoa seedlings of hybrid UITlxNa32 inoculated with Glomus mosseae and Scutellospora calospora either as a single inoculum or as a mixed inoculum and uninoculated control were grown in 2 kg sterilized Tai Tak. series soil. The experiment was a single factor experiment arranged in a completely randomized design, with type of inoculum as a factor with four replications. The trial was done in greenhouse No. 11 C of Univeristi Pertanian Malaysia. Of the four treatments used, plants inoculated with mixed inoculum gave more pronounced and significant vegetative growth (as measured by plant height, total leaf area, root dry weight and nutrient content in leaf tissue) compared to the other treatments. The effect of mixed inoculum G. mosseae and S. calospora was further evaluated in the field using a split-plot design, with V AM treatment as the main plot and cocoa clone as the subplot Five selected cocoa clones (KKM3, KKM4, KKM5, PBC137 and PBC 178) were grafted onto nine year old cocoa trees from hybrid UITlxNa32. All data were collected at 3, 5 and 7 months after VAM inoculation. Inoculated clones showed better and significant plant growth, with longer scion lengths and larger leaf area index, than uninoculated ones. The crop physiology was also significantly affected by VAM, with higher relative water and chlorophyll content in the leaf and lower stomatal resistance. Results obtained also indicated that the mixed inoculum significantly improved VAM development in the soil, subsequently enhancing P, K and Mg uptake by the plants. This subsequently shortened the plant vegetative phase enabling them to flower earlier. 1bis is true for the PBC clones. In fact, between the two clones tested, the PBC clones-especially PBC 137 proved to be far superior than the KKM clones. Soil physical properties such as soil moisture, percent aggregate and aggregate stability were also improved in the presence of the mycorrhiza fungi. The difference between treatments however was not significant.